Expression of neuron-specific enolase in multiple myeloma and implications for clinical diagnosis and treatment. - Haiping Yang; Ruihua Mi; Qian Wang; Xudong Wei; Qingsong Yin; Lin Chen; Xinghu Zhu; Yongping Song (PLoS ONE)
Objective To determine the expression of neuron-specific enolase (NSE) in patients with multiple myeloma (MM) and to evaluate its clinical value as a tumor marker and, an indicator of disease progression and treatment efficacy. Methods Using electrochemiluminescence immunoassay (ECLIA), we measured the serum levels of NSE in 47 healthy subjects (control group), 25 patients with small cell lung cancer (lung cancer group), and 52 patients with MM (MM group). For the MM group, serum NSE levels were measured and other disease indicators and related symptoms were monitored before and after chemotherapy. The relationship between NSE expression and other MM-related factors was analyzed. In addition, immunohistochemical staining was performed on bone marrow biopsy specimens from patients with MM. Results In the control group, serum NSE levels were within the normal range as previously reported, while the lung cancer group and the untreated MM group exhibited NSE levels that were significantly higher relative to the control group (P<0.05). The difference in NSE expression between the lung cancer group and untreated MM group was statistically significant (P<0.05). NSE levels were significantly decreased in MM patients after chemotherapy and were positively correlated with an MM disease index [beta-2 microglobulin (β2-MG)]. Changes in NSE were not related to the response rate to chemotherapy but rather were correlated with progression-free survival. Conclusions Patients with MM may have increased serum NSE levels, and changes in NSE may provide insight into treatment efficacy of chemotherapy and disease progression. Perhaps NSE expression is a viable biomarker for MM and can be a useful reference for the design and adjustment of clinical MM treatment programs.